2016
DOI: 10.1371/journal.pone.0143869
|View full text |Cite
|
Sign up to set email alerts
|

Broad Range of Hepatitis B Virus (HBV) Patterns, Dual Circulation of Quasi-Subgenotype A3 and HBV/E and Heterogeneous HBV Mutations in HIV-Positive Patients in Gabon

Abstract: Integrated data on hepatitis B virus (HBV) patterns, HBV genotypes and mutations are lacking in human immunodeficiency virus type 1 (HIV-1) co-infected patients from Africa. This survey was conducted in 2010–2013 among 762 HIV-1-positive adults from Gabon who were predominantly treated with 3TC-based antiretroviral treatment. HBV patterns were identified using immunoassays detecting total antibody to hepatitis B core antigen (HBcAb), hepatitis B surface antigen (HBsAg), IgM HBcAb, hepatitis B e antigen (HBeAg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
(51 reference statements)
2
15
1
Order By: Relevance
“…Other studies have reported primary 3TC resistance due to rt181T/S substitutions [10]. HBV mutations also occur in the absence of 3TC therapy and are thought to occur naturally in HBV carriers who have not been treated with the drug, implying that pre-existing mutations may be transmitted or contribute toward early emergence of 3TC resistance during therapy [11, 12]. …”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported primary 3TC resistance due to rt181T/S substitutions [10]. HBV mutations also occur in the absence of 3TC therapy and are thought to occur naturally in HBV carriers who have not been treated with the drug, implying that pre-existing mutations may be transmitted or contribute toward early emergence of 3TC resistance during therapy [11, 12]. …”
Section: Introductionmentioning
confidence: 99%
“…The increase of genotype N86 has been associated with a decreased susceptibility to artemisinins in vitro [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Previous sero‐epidemiological studies conducted between 1988 and 2009 in Gabon showed a high prevalence of HBsAg (>8%) in various populations within the provinces of Haut‐Ogooué, Ngounié, Woleu‐Ntem and Ogooué‐Ivindo and that about 60.0% of HBsAg positive individuals in Woleu‐Ntem had antibodies to HDV . In these few, often restricted, study populations, circulation of HBV genotypes A3, A4, and E and HDV genotypes 1, 7, and 8 were reported …”
Section: Introductionmentioning
confidence: 93%
“…[23][24][25][26] In these few, often restricted, study populations, circulation of HBV genotypes A3, A4, and E and HDV genotypes 1, 7, and 8 were reported. [24][25][26][27][28] Screening for HBV is carried out mainly in blood transfusion centres, after blood exposure accidents or in symptomatic patients (clinical jaundice) but broad therapeutic coverage does not extend to patients living in rural areas, despite a national policy of Universal Health Coverage and the existence of a social health insurance. Furthermore, HBV vaccination has been implemented in infants in urban areas in Gabon since 2005, with an estimated immunization coverage between 71% to 82%, and to date, there is no HBV vaccination program in rural areas.…”
mentioning
confidence: 99%